2017
DOI: 10.5463/dcid.v28i1.584
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Music Intervention on the Behaviour Disorders of Children with Intellectual Disability using Strategies from Applied Behaviour Analysis

Abstract: Purpose: The effect of music intervention on mild and moderate Intellectually disabled children was studied in non-randomized pre-test post-test control group design at an Indian state (Jammu) J&K.Method: The mild and moderate intellectual disabled children fulfilling inclusive and exclusive criteria were placed into control and experimental group. BASIC-MR part-B (pre-test) was administered on both the groups. Intervention in music activities using strategies from Applied Behaviour Analysis was introduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
(6 reference statements)
0
11
0
Order By: Relevance
“…Twenty‐three studies targeted children with disabilities (Abazari et al, 2017 ; Dai et al, 2018 ; De Villiers et al, 2013 ; Devries et al, 2018 ; Esmaili et al, 2019 ; Golzari et al, 2015 ; Juneja et al, 2012 ; Kalgotra & Warwal, 2017 ; Karanth et al, 2010 ; Koo & Thomas, 2019 ; Lal, 2010 ; Lee et al, 2019 ; Liang et al, 2022 ; Manohar et al, 2019 ; McConachie et al, 2000 ; Nair et al, 2014 ; Pajareya & Nopmaneejumruslers, 2011 ; Pop et al, 2013 ; Rahman et al, 2016 ; Shin et al, 2009 ; Shore & Juillerat, 2012 ; Wang, 2008 ; Zuurmond et al, 2018 ). Twelve studies targeted adults with disabilities (Amaresha et al, 2018 ; Govindaraj et al, 2018 ; Hanlon et al, 2020 ; Karaman et al, 2020 ; Khalil et al, 2019 ; Li et al, 2018 ; Lund et al, 2013 ; Rami et al, 2018 ; Ran et al, 2003 ; Ravindren et al, 2018 ; Shore & Juillerat, 2012 ; Yildiz et al, 2004 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty‐three studies targeted children with disabilities (Abazari et al, 2017 ; Dai et al, 2018 ; De Villiers et al, 2013 ; Devries et al, 2018 ; Esmaili et al, 2019 ; Golzari et al, 2015 ; Juneja et al, 2012 ; Kalgotra & Warwal, 2017 ; Karanth et al, 2010 ; Koo & Thomas, 2019 ; Lal, 2010 ; Lee et al, 2019 ; Liang et al, 2022 ; Manohar et al, 2019 ; McConachie et al, 2000 ; Nair et al, 2014 ; Pajareya & Nopmaneejumruslers, 2011 ; Pop et al, 2013 ; Rahman et al, 2016 ; Shin et al, 2009 ; Shore & Juillerat, 2012 ; Wang, 2008 ; Zuurmond et al, 2018 ). Twelve studies targeted adults with disabilities (Amaresha et al, 2018 ; Govindaraj et al, 2018 ; Hanlon et al, 2020 ; Karaman et al, 2020 ; Khalil et al, 2019 ; Li et al, 2018 ; Lund et al, 2013 ; Rami et al, 2018 ; Ran et al, 2003 ; Ravindren et al, 2018 ; Shore & Juillerat, 2012 ; Yildiz et al, 2004 ).…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies reported on interventions which targeted individuals with a single type of impairment, with only one reporting on an intervention for people with a range of impairments (Devries et al, 2018 ). Twenty studies targeted people with intellectual disabilities (Abazari et al, 2017 ; Azari et al, 2019 ; Dai et al, 2018 ; Devries et al, 2018 ; Esmaili et al, 2019 ; Golzari et al, 2015 ; Juneja et al, 2012 ; Kalgotra & Warwal, 2017 ; Karanth et al, 2010 ; Koo & Thomas, 2019 ; Lal, 2010 ; Lee et al, 2019 ; Liang et al, 2022 ; Manohar et al, 2019 ; Nair et al, 2014 ; Pajareya & Nopmaneejumruslers, 2011 ; Pop et al, 2013 ; Rahman et al, 2016 ; Shin et al, 2009 ; Wang, 2008 ). Thirteen studies reported on interventions which targeted people with psychosocial/mental impairments (Amaresha et al, 2018 ; Govindaraj et al, 2018 ; Hanlon et al, 2020 ; Karaman et al, 2020 ; Khalil et al, 2019 ; Li et al, 2018 ; Li et al, 2019 ; Lund et al, 2013 ; Rahmani et al, 2015 ; Rami et al, 2018 ; Ran et al, 2003 ; Ravindren et al, 2018 ; Yildiz et al, 2004 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the emotional component, many studies suggested that music therapy had a positive impact on the person with an intellectual disability, including a decrease in disruptive behaviours (Coyle, 2011; Hoyle & McKinney, 2015; Jaschke & Scherder, 2015; Kalgotra & Warwal, 2017; Savarimuthu & Bunnell, 2002; Urpi, 2016) and anxiety (Agheana, 2017; Hooper & Lindsay, 1990; Perry, 2003; Watson, 2016), increase in self‐esteem (Almeida et al, 2011; Coyle, 2011; Detzner, 1997; Hatampour et al, 2011; Humpal, 1991; Lewis, 2019; Moceviciene & Prudnikova, 2015; Rickson & Warren, 2018; Savarimuthu & Bunnell, 2002; Sooful et al, 2013; Wilson & MacDonald, 2019), and improved self‐expression and management of emotions (Cameron, 2017; Coyle, 2011; Graham, 2004; Savarimuthu & Bunnell, 2002; Staab &Dvorak, 2019; Tyas, 2010; Urpi, 2016). Beneficial outcomes for the development of social skills were also found in many studies (Agheana, 2017; Agrotou, 1994; Duffy & Fuller, 2000; Graham, 2004; Hashemian & Mohammadi, 2015; Hoyle &McKinney, 2015; Humpal, 1991; McLaughlin & Adler, 2015; Rickson & Warren, 2018; Surujlal, 2013).…”
Section: Resultsmentioning
confidence: 99%